Evaluating the impact of a multimodal perinatal education program on birth preparedness, mental health, and birth outcomes among rural primiparous women: a retrospective cohort study - Wei Li; TaiFang Ren; GuiHong Xu; YongShu Wang (BMC Pregnancy and Childbirth)
Abstract Background Perinatal education programs play a crucial role in enhancing maternal knowledge and practices related to childbirth, particularly among rural populations. This study aims to assess the impact of a holistic perinatal education program on birth preparedness, mental health, and birth outcomes among rural primiparous women. Methods A retrospective cohort design was employed, utilizing patient records from Third Affiliated Hospital of Xinxiang Medical University between January 2021 and December 2022. A total of 149 rural primiparous women, aged 18–49 years with a rural household registration, were identified and categorized into two groups: the Intervention Group (n = 77), exposed to the perinatal education program, and the Control Group (n = 72), not exposed. The program encompassed physical workshops, a digital learning platform, and personalized counseling sessions. Outcome measures included Birth Preparedness and Complication Readiness (BPCR) scores, mental health metrics (BDI-II for depression and STAI-S for anxiety), and birth outcomes. Results The Intervention Group demonstrated significant improvements in BPCR knowledge scores (P < 0.001) and practice scores (P = 0.047) post-intervention. A reduction in depressive (P = 0.021) and anxiety symptoms (P = 0.017) was also observed in the Intervention Group over time. There were significant differences in the mode of delivery and reasons for cesarean deliveries between the groups, with a higher rate of vaginal births (P = 0.035) and fewer maternal indications for cesareans (P = 0.021) in the Intervention Group compared to the Control Group. Conclusion The holistic perinatal education program shows a positive impact on birth preparedness, mental health, and birth outcomes among rural primiparous women. Such programs could be crucial in empowering women in rural settings, enhancing their preparedness for childbirth, and improving maternal mental health.